THERMODYNAMIC PROPERTIES OF SURFACE SPECIES AT THE MINERAL-WATER INTERFACE UNDER HYDROTHERMAL CONDITIONS: A GIBBS ENERGY MINIMIZATION SINGLE-SITE 2PKA TRIPLE-LAYER MODEL OF RUTILE IN NACL ELECTROLYTE TO 250°C - Kulik D.A. (My University, 2000)
Standard partial molal thermodynamic properties of surface species in a single-site 2pKA triple-layer model (TLM) for rutile in NaCl electrolyte, consistent with the SUPCRT92-98 data, were estimated at temperatures T = 0 to 250°C and saturated vapor pressure PSAT using a Gibbs energy minimization (GEM) approach (Kulik, 1999) and hydrothermal potentiometric titration data (Machesky et al., 1998a). Evaluation strategy was based on conventional setting to zero of standard state entropy and heat capacity effects of the ''surface hydronium desorption'' reaction >O0.5H2+ = >O0.5H0 + Haq+, with one-term temperature extrapolation appropriate. The standard state properties of the ''surface water dissociation'' reaction >O0.5H0 = >O0.5- + Haq+ in a three-term extrapolation, with Cp^o298(>O0.5-) assumed equal to Cp^o298(OHaq-) and ΔS^o298 estimated from enthalpy of rutile surface protonation in water ΔH^oprot,298, yielded a very good match of predicted pristine point of zero charge (pHPPZC) and measured point of zero charge (pHPZC) on rutile to T = 250°C. Correlation of ΔH^oprot,298 for various oxides versus pHPPZC suggests that the entropy ΔS^oprot,298 = 25 +/- 4 J K-1 mol-1 may be constant for all oxide surfaces, pHPPZC(T) be hence a function of pHPPZC at T0 = 25°C only: pHPPZC,T = -29.134 + T0/T(pHPPZC,T0 + 3.2385) + 4.545ln T.The standard partial molal properties of Na+ and Cl- outer-sphere surface complexes on rutile were estimated from GEM TLM fits of potentiometric titration data at different T and mNaCl. Adjustable parameters were: standard partial molal Gibbs energy g0(>O0.5-Na+), interdependent with inner capacitance density C1 (increasing from 1.6 F . m-2 at 25°C to 2.3 F . m-2 at 250°C), and maximum site density Γmax(>O0.5H2+Cl-). No surface activity term (SAT) ln Ξ = f(Γmax) corrections were needed for >O0.5-Na+ species, i.e., Na+ adsorption on rutile occurs in the ''TLM ideal region'' up to 300°C and 1 m NaCl.